Analisis Penggunaan Aplikasi Tiktok Terhadap Minat Konsumen Berbelanja dalam Ekonomi Islam - Indra Saputra; Herlina Yustati (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Social media is the most popular media and can be used by children and adults. Social media has become very popular because it provides convenience in conducting various communications. Uniquely, users do not need to switch to other applications to shop. This study aims to determine the use of TikTok Shop on consumer behavior of Sharia Economics students’ class of 2022 at UIN Fatmawati Sukarno Bengkulu in purchasing food and beverage products. The method in this study is qualitative with a descriptive approach. where qualitative research is research that intends to understand the phenomenon of what is experienced by the research subject, such as behavior, perception, motivation, action, holistically, by utilizing various methods in the descriptive approach that is studied and elaborated by providing an explanation of an issue or problem being studied. The conclusion in this study is that many students use the TikTok Shop application to shop for fashion products, because the TikTok Shop application is very practical and easy to use. From the results of research in the field, it can be concluded that the majority of UIN Fatmawatti Sukarno Bengkulu students who shop at Tiktok Shop are because of the quality and comfort when shopping. In addition, the results obtained were not disappointing. Respondents can also enjoy entertainment while they shop, which they don't get on other E-commerce platforms.